mm-Wave Antennas For Satellite And Mobile Communications - Greco, Francesco; Crupi, Felice; Amendola, Giandomenico (My University, 2017)
Ever growing demands for higher data rate and bandwidth are pushing wireless applications to millimetre-wave band (3-300GHz), where sufficient bandwidth is available and high performance can be achieved without using complex modulation systems. In addition to Telecom applications, millimetre-wave bands has enabled novel short range and long range radar sensors for automotive as well as high resolution imaging systems for medical and security. The major obstacle for the wide deployment of commercial wireless and radar systems in this frequency range is the high cost of the overall system. The main object of this work is to investigate and to develop different type of antenna that could be applied in satellite communications, in the future fifth generation of mobile networks and on radar automotive systems. In particular, in the present thesis, four antennas have been developed. A dual band dual polarized antenna array for Satcom-On-The-Move application that gives the possibility to obtain a fixed beam on the frequency range 19-21GHz (Rx band) and 29-31GHz (Tx band). This structure could be used in association with a fully mechanical pointing system. A Reflector terminal in the Q/V bands that could be use on the backhaul point of the 5G future architecture. A Ka band scaled version of the antenna has been realized and measured proving that it can be a valid solution for compact earth terminals. A novel reflectarray with potential applications in both satellite communications and high speed point-to-point radio links. Finally, a 77GHz transmit-array antenna mounted on a QFN package. This kind structure, due to the compact dimensions, could be represent a possible solution for automotive radar system
Dottorato di Ricerca in Information and Communication Engineering For Pervasive Intelligent Environments, Ciclo XXIX
Keywords: Artificial satellites in telecomunication; Mobile comunication systems; Millimeter waves